HUBUNGAN CARA BELAJAR DENGAN HASIL BELAJAR IPA SISWA KELAS V DI SD GUGUS I KECAMATAN TAMPAN KOTA PEKANBARU - Jumiar Khairiah; Mahmud Alpusari; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Factors can affect student learning outcomes is internal factors and external factors. Learning strategy is one of the internal factors that can affect student learning outcomes. Because of this, the main objective of this research is to know the a significant relationship between the learning strategy with learning outcames of science grade V in elementary school gugus I of tampan district of pekanbaru city. The type and method used in the research is quantitative with correlationl method. This research is carried out In Elementary School Gugus I of Tampan District of Pekanbaru City 4 elementary school. The elementary school that is, the elementary school 136 pekanbaru, the elementary school 37 pekanbaru, the elementary school darul hikmah, and the elementary school teknologi, with total sample as many as 169 students, using the technique of simple random sampling. The data collecting technique used is the technique questionnaire and documentation. Research data were analyzed using the Pearson Product Moment Correlation test, coefficient determination test, significance test with significant level α = 0.05. the results of the analysis of data obtained tcount of 19,37 and ttable of 1,960. the results show that there is a significant relationship between the learning strategy with learning outcames of science grade V in elementary school gugus I of tampan district of pekanbaru city. Then rcount of = 0,832 which means it has a degree of relationship that is very strong and its contribution of 69,22%.Key words: learning strategy, learning outcames of science